Modelling the construction and long-term response of Göta Tunnel. (June 2021) - Tornborg, Johannes; Karlsson, Mats; Kullingsjö, Anders; Karstunen, Minna
Abstract: This paper presents a benchmark of a rate-dependent constitutive model for soft soils, implemented in a 2D finite element code, against the response of an instrumented excavation in sensitive clay: Göta Tunnel in Gothenburg. The monitoring data, which comprise time-series of pore water pressures, displacements, earth pressures and strut forces, provide valuable insights of the time-dependent response during the construction period. The long-term response, in terms of the ongoing settlement rates, is assessed using remote sensing data. The results of the numerical simulations demonstrate that the constitutive model, Creep-SCLAY1S, is capable of capturing the observed response. The trends of vertical and horizontal displacements are captured well until the stage of dewatering, and the evolution of pore pressures and earth pressures is computed with high accuracy, excluding peaks in the measurement values arising from pile and rock anchor installation. Most importantly, the results demonstrate that the rate-dependent model enables to model the complete service life of the tunnel, from construction of the excavation to the tunnel operation, with one unified model parameter set. Furthermore, the comparisons highlight the importance of assessing installation effects both in the choice of construction methods and modelling.